The Strength Within: CSR Governance as an Environmental Performance Driver in Weak Institutional Contexts - Eun-jung Hyun; Si Yu (Systems)
This study investigates how the relationship between firm-level corporate social responsibility (CSR) governance and corporate environmental performance (CEP) varies across diverse national contexts. Drawing on institutional theory, organizational adaptation theory, and the concept of institutional voids, we analyze an extensive dataset of 5326 firms from 26 OECD countries over a seven-year period (2013–2019). Employing panel data analysis, we examine the moderating effects of country-level factors on the CSR governance–CEP relationship. Our findings reveal a significant positive association between a firm’s CSR governance quality and environmental performance, which is notably stronger in countries characterized by weaker environmental governance, less prominent societal environmental values, and fewer climate mitigation laws and policies. These results suggest that firms with strong CSR governance effectively fill institutional voids in environmental governance, going beyond mere compliance to drive environmental performance improvements where external pressures are weak. Our study contributes to the literature by advancing the current understanding of the contextual nature of CSR, extending the application of institutional void theory to environmental governance landscapes in developed economies, and providing a more nuanced perspective on when and where CSR governance matters most for environmental outcomes. These insights offer valuable implications for managers in diverse institutional contexts and for policymakers seeking to enhance corporate environmental performance through complementary governance mechanisms.